Quality assessment of an Ultra-Wide Band positioning system for indoor wheelchair court sports - Perrat, Bertrand; Smith, Martin J.; Mason, Barry S.; Rhodes, James M.; Goosey-Tolfrey, Victoria L. (SAGE, 2015)
Ultra-Wide Band radio positioning systems are maturing very quickly and now represent a good candidate for indoor positioning. The aim of this study was to undertake a quality assessment on the use of a commercial Ultra-Wide Band positioning system for the tracking of athletes during indoor wheelchair court sports. Several aspects have been investigated including system set-up, calibration, sensor positioning, determination of sport performance indicators and quality assessment of the output. With a simple set-up procedure, it has been demonstrated that athletes tracking can be achieved with an average horizontal positioning error of 0.37 m (s = 6 0.24 m). The distance covered can be computed after data processing with an error below 0.5% of the course length. It has also been demonstrated that the tag update rate and the number of wheelchairs on the court do not affect significantly the positioning quality; however, for highly dynamic movement tracking, higher rates are recommended for a finer dynamic recording.